Re-assessing the Contribution of Energy Consumption to GDP Per- Capita: Evidence from Developed and Developing Countries - Abbas, Zaheer (International Journal of Energy Economics and Policy, 2020)
After the math of 1970's, various theories of macroeconomics argued that, like capital and labor, energy use as a factor of production has a contribution to increase the GDP. This study explores energy- GDP per capita relationship in 78 countries over the period: 1980-2014. ARDL co-integration approach is applied in pure time-series setting for each country as well as in panel data setting separately for developed and developing countries. The results confirm the presence of a positive relationship between energy consumption and GDP per capita in both the categories of countries. However, to what extent energy consumption affects GDP per capita varies both between and within the two categories of countries. Results from time-series ARDL analysis justify panel ARDL analysis. Specifically, the contribution of energy consumption to GDP per capita is higher in developed countries as compared to developing countries. The study concludes that the efforts of developing countries to sustain their living standard, Energy consumption per capita is the crucial, Further, the findings lessened to developing countries to increase the energy consumption per capita thereby increase the GDP per capita. Keywords: Energy Consumption, GDP Per-Capita, ARDL, Developed & Developing Countries. JEL Classifications: Q430, C32, C33 DOI: https://doi.org/10.32479/ijeep.9803